Report on the Conference of History of Mathematics and Teaching of Mathematics: research in History of Mathematics and Teaching of Mathematics : University of Szeged 19-23 May, 2010, Szeged, Hungary (Teaching Mathematics and Computer Science, 2010)
The 6th Conference on the History of Mathematics and Teaching of Mathematics was held in Szeged (Hungary). Its motto reads as:Mathematics – a common language for Europe for thousand years.The aim of the conference was to present aspects of History of Mathematics, including its impact on Teaching of Mathematics, to provide a forum to meet each other, and to give an opportunity for young researchers to present their results in these fields. University colleagues, students, graduate students and other researchers were invited. The programme of the Conference included talks and posters. The abstracts of the lectures and the posters are presented in this report. There were 24 presentations and poster lectures.